Design and implementation of a pic-based inductive human praying postures recognition system - Larbani, Sofiane (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This dissertation explore and discuss the design and implementation of an inductive transducer-based recognition system used for identifying different postures being assumed during praying. The body, moving up and down, is assuming relevant posture positions that can cause a change in inductive element, representative of these postures positions. When processed by a PIC32 microcontroller programmed to act as Data Acquisition System (DAS), these inductive changes can be made to produce signal waveforms signature of these postures. This system is composed of a modified sensor which is an inductive loop that has an inner rectangular loop inside the outer loop. The double loop transducer is reported to be more sensitive than the rectangular conventional shape reported in very recent work. The overall system is thus composed of nine (9) such loops buried under a prayer mat, all interfaced through their respective conditioning circuits to the PIC32 based development board (ChipKit Max32), connected to a laptop through its USB port. The loops are divided into three (3) main zones; each of the first two zones recognizes one posture position (either Wuquf or Rokoo) each while last zone is to recognize signals for two postures of Qood and Sojod. The signals so received from the conditioning system at the ADC of MAX32, are processed and then sent to the computer using its USB port. Using MATLAB, the collected signals are processed to be displayed for every zone and loop. The parameter associated to the recognition of each posture waveform and respective amplitude, are then detected such that respective postures are identified as a result, in occurring in loops, of changes affecting the waveform shape and amplitude. The design is simulated using NI MULTISIM tool, the obtained results are supported by the theoretical and analytical derivations, and the simulation matched the experimental results obtained through a microcontroller-based system. This system has the potential of being used for monitoring purposes by identifying postures during times such as the sleeping by fitting the detecting loops to suitable places under the bed for medical purposes.